Effectiveness of Colored Stick In Improving Addition Skills for Deaf Children - Aiyouti, Cahaya Sha’adah; Zulmiyetri, Zulmiyetri; Iswari, Mega; Budi, Setia (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to investigate the effectiveness of colored sticks in improving lateral addition skills, with sums ranging from more than 10 to 20, among sixth-grade deaf students at SLB Hikmah Reformasi Padang. The research employs an SSR approach with an A-B-A design. It consists of 13 sessions divided into three phases. The first phase, baseline (A1), spans 3 meetings, showing stable results with a score of 20. The second phase, intervention (B), lasts for 7 meetings, indicating improvement with scores increasing from 30 to 75 and demonstrating stability from the 9th to the 10th meeting. The final phase, another baseline (A2), takes place over 3 meetings, showing stable results with a score of 90 in the 12th and 13th meetings. These findings indicate an enhancement in addition skills, with results up to 20, using colored sticks among deaf children.